2019
DOI: 10.1177/0309524x19891672
|View full text |Cite
|
Sign up to set email alerts
|

Wind power forecasting: A systematic literature review

Abstract: Accurate and reliable prediction of wind energy in the short term is of great importance for the efficient operation of wind farms. One of the procedures to search for, summarize, organize and synthesize existing information is a systematic literature review. In this article, we present a systematic literature review on the predictive models of wind energy, aiming to establish the baseline for the development of a short-term wind energy prediction model that employs artificial intelligence tools to be applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…A systematic literature review for wind power forecasting by Maldonado-Correa et al (2019) confirmed that ANNs are considered the most frequently applied intelligence models in the literature studies for wind power forecasting in the past 5 years. These networks provided adequate results because of their ability to capture non-linearity in wind patterns, especially for short-term and medium-term forecasting (Du et al, 2019;Maldonado-Correa et al, 2019). The simplest type of ANNs is the feed-forward NN (FFNN; Nielson et al, 2020), this network was used to predict a monthly energy production of 2.5 MW of a wind turbine.…”
Section: Ann For Wind Power Forecastingmentioning
confidence: 85%
“…A systematic literature review for wind power forecasting by Maldonado-Correa et al (2019) confirmed that ANNs are considered the most frequently applied intelligence models in the literature studies for wind power forecasting in the past 5 years. These networks provided adequate results because of their ability to capture non-linearity in wind patterns, especially for short-term and medium-term forecasting (Du et al, 2019;Maldonado-Correa et al, 2019). The simplest type of ANNs is the feed-forward NN (FFNN; Nielson et al, 2020), this network was used to predict a monthly energy production of 2.5 MW of a wind turbine.…”
Section: Ann For Wind Power Forecastingmentioning
confidence: 85%
“…Due to the variable nature of solar and wind power generation, ML has been used extensively to construct short-term forecasts of these quantities, as described in other reviews (42)(43)(44)(45). Mirroring the above discussion of trends in demand estimation, some trends in solar and wind power estimation include disaggregating power generation to obtain real-time estimates, as well as employing innovative features or structural information for short-term forecasts.…”
Section: Solar and Wind Power Estimationmentioning
confidence: 99%
“…A number of studies have been found to be related to short-term forecasting models of wind power generation capacity [10]. The researchers, in [11] introduced short-term wind speed forecasting of wind farms based on the least squares support vector machine (SVM) model.…”
Section: Introductionmentioning
confidence: 99%